A process-model-free method for model predictive control via a reference model-based proportional-integral-derivative controller with application to a thermal power plant - Shi, Gengjin; Ma, Miaomiao; Li, Donghai; Ding, Yanjun; Lee, Kwang Y. (Frontiers in Control Engineering, 2023)
Model predictive control (MPC) is an advanced control strategy which can achieve fast reference tracking response and deal with process constraints, time delay and multivariable problems. However, thermal processes in coal-fired power plants are usually difficult to model accurately, which limits the application of MPC to thermal power plants. To solve aforementioned problem, this paper proposes a process-model-free method for MPC via a reference model (RM)-based controller——desired dynamic equational (DDE) proportional-integral-derivative (PID) controller (MPC-DDE). The DDE-PID can provide the design model and enhance the disturbance rejection ability for MPC. Simulations and results of field tests on a coal-fired unit show the superiorities of the proposed controller in reference tracking, disturbance rejection and robustness, which indicates the promising prospect of the field application of MPC-DDE to thermal power plants.